Synthesis and Semi-conducting Properties of Novel 2-(4-Chloro-1-naphtyloxy)-2-oxoethyl Methacrylate with 2-(Dimethylamino)Ethyl Methacrylate Copolymers, Quaternized Amino Groups - Soykan, Cengiz; Sahan, Ahmet; Yakuphanoğlu, Fahrettin (Taylor & Francis Inc, 2011)
Methacrylate based monomer, 2-(4-chloro-1-naphtyloxy)-2-oxoethyl methacrylate (ClNOEMA) was synthesized by reacting 4-chloro-1-naphthyloxychloromethylketone with sodiummethacrylate in acetonitrile solvent at 70 degrees C in the presence of triethylbenzylammonium chloraid as phase transfer matter. The free-radical initiated copolymerization of (ClNOEMA), with 2-(dimethylamino) ethyl methacrylate (DMAEMA) was carried out in 1,4-dioxane solution at 70 +/- 1 degrees C using 2,2'-azobisisobutyronitrile (AIBN) as an initiator with 50%-50% monomer-to-monomer ratio in the feed. This copolymer has been converted into a novel salts by reaction with the iodemethane (CH3I). The copolymers and the corresponding salts have been characterized fully by a range of spectroscopic and thermal analysis techniques. The electrical conductivity dependence of temperature of the polymers were measured and the polymers exhibit the semiconducting behavior, confirming that the electrical conductivity increases with increasing temperature. The poly(CINOEMA-co-DMAEMA) polymer doped by CH3I for 5 min shows the highest conductivity. The optical band gap, activation energy and room temperature conductivity values of this polymer were obtained to be 2.16 eV, 0.141 eV and 3.9x10(7) S/cm, respectively. These electronic parameters suggest that the poly(CINOEMA-co-DMAEMA) [0.23:0.77] polymer doped by CH3I for 5 min is an organic semiconductor with the thermally activated conduction mechanism.
Keywords: 2-(4-chloro-1-naphtyloxy)-2-oxoethyl methacrylate; semi-conducting polymers; the electrical; optical and thermal properties